The Effect of Environmental Performance on The Value of The Company with Financial Performance as an Intervening Variable - Dewi Ari Ani (Jibaku: Jurnal Ilmiah Bisnis, Manajemen dan Akuntansi, 2021)
The purpose of this study is to test and analyze environmental performance as an independent variable against the value of the company as a dependent variable with financial performance as an intervening variable. This study used the population of all manufacturing companies in the chemical and basic industrial sectors as well as mining companies listed on the Indonesia Stock Exchange and ranked in proper in 2016-2018. This study uses Path Analysis as a method of data analysis. This study uses PROPER ratings published by the Ministry of Environment as a proxy of environmental performance variables. The Tobins'Q ratio in this study was used as a proxy of the company's value variable and Return On Equity (ROE) as a proxy of the financial performance variable. From the results of tests and analysis that have been conducted concluded that environmental performance has a significant impact on financial performance, environmental performance has a significant effect on the value of the company and environmental performance does not significantly affect the value of the company with financial performance as an intervening variable.Keywords: Environmental Performance, Financial Performance, Corporate Value.